تأثير برنامج مقترح وفق اسلوب التعلم النشط بالتحصيل الحركي لمهارة التصويب من السقوط بكرة اليد لدى الطلاب - غريب, فرهنط فرج حممد; خان, بيباك حممد علي; محمود, هةلاَلَة برهان (Sulaimani Journal for Humanities, 2018)
The aim of the research is identifying the influence of active learning method in motor achievement for shooting skill by falling in hand ball game for students the sample of the research intentionally has been selected from second stage students / Basic Education Department / Sulaimani University for academic year (2014-2015) and the sample of the research selected by lot between groups which group (B) became experimental group, and group (A) became controlled group (10) students for each group (2) educational units per week for (4) weeks the research has been done by experimental program two groups (experimental, controlled) pre and post tests and the researchers concluded improvement and development in motor achievement in shooting skill according to the used method the researchers recommended the necessary of using active learning method through learning shooting skill and other skills